2017
DOI: 10.12944/crnfsj.5.3.16
|View full text |Cite
|
Sign up to set email alerts
|

A Potential of Coleus Tuberosus Crackers Rich in Resistant Starch Type 3 Improves Glucose and Lipid Profile of Alloxan –Induced Diabetic Mice

Abstract: This study aims to determine the consumption effect of Coleus tuberosus flour and crackers rich in resistant starch type 3 to glucose and lipids profiles in diabetic mice. The study was conducted with four treatments (normal mice with AIN 93 diet, diabetic mice with AIN 93 diet, diabetic mice with Coleus tuberosus flour diet, diabetic mice with coleus tuberosus crackers rich in resistant starch type 3). The analysis of blood glucose levels and lipids profile were determined using an enzymatic colorimetric meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Previous study has demonstrated that specific fibers such as resistant starch increased C4 formation by the microbiota . Biscuits rich in resistant starch type 3 improved glucose and lipid profiles in diabetic mice . Furthermore, a positive correlation between starch‐rich food consumption and increased number of HDL particles was observed, this correlation resulted in lipid profile improvement …”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Previous study has demonstrated that specific fibers such as resistant starch increased C4 formation by the microbiota . Biscuits rich in resistant starch type 3 improved glucose and lipid profiles in diabetic mice . Furthermore, a positive correlation between starch‐rich food consumption and increased number of HDL particles was observed, this correlation resulted in lipid profile improvement …”
Section: Discussionmentioning
confidence: 79%
“…30 Biscuits rich in resistant starch type 3 improved glucose and lipid profiles in diabetic mice. 31 Furthermore, a positive correlation between starch-rich food consumption and increased number of HDL particles was observed, this correlation resulted in lipid profile improvement. 32 In summary, we have shown that amoxicillin treatment has either direct effects on lowering ApoA-I transcription and secretion or indirect effects via modified SCFA concentrations, because SCFA were found to stimulate hepatic ApoA-I expression.…”
Section: Discussionmentioning
confidence: 92%
“…Nugraheni et al, 10 and A. Kanchana et al, 11 used resistant starch type 3 (RS3) andoryza sativa (red rice)flakes to make crackers and snacks that can as a functional food to improve diabetes, obesity and metabolism.Timbadiya et al, 12 replaced with peanut butter to reduce saturated fatty acids in cookies not only had a greater appreciable sensory quality, but also reduce heart disease risk through consumption of beneficial mono and poly unsaturated fats. Ajanaku et al, 13 indicated the maize-Ogi with abundant protein sources would as an alternative approach for combating the threats of protein malnutrition in neonates.Further, Biswas et al, 14 evidenced the hypoglycemic and hypolipidemic efficiency ofvaluable components from watermelon (Citrullus vulgaris) seed kernel sonmale albino rats.…”
Section: Editorialmentioning
confidence: 99%
“…Extrusion technology is used to manufacture grains such as analog rice. This process tends to increase resistant starch (Raigond et al, 2015), which has functional properties to lower cholesterol and glycemic indexes, and to improve insulin sensitivity (Bindels et al, 2017;Jyoshna and Hymavathi, 2017;Nugraheni et al, 2017). Some types of legumes used for analog rice, such as Glycine max (Ciabotti et al, 2016), Phaseolus vulgaris (Sai-Ut et al, 2009), Vigna radiata (Dahiya et al, 2015), and Vigna unguiculata (Devi et al, 2015), are sources of dietary fiber.…”
Section: Introductionmentioning
confidence: 99%